Concurrent benign metastasizing leiomyoma in the lung and lumbar spine with elevated standardized uptake value level in positron-emission tomography computed tomography: A case report and literature review. Issue 27 (July 2018) - Zong, Dandan; He, Wenlong; Li, Jinhua; Peng, Hong; Chen, Ping; Ouyang, Ruoyun
Abstract: Rationale: Benign metastasizing leiomyoma (BML) is rare condition involving distant metastases secondary to benign uterine leiomyoma, and it is most commonly found in the lungs. It rarely metastasizes to the spine to cause osteolytic damage and spinal canal compression. Patient concerns: A 51-year-old woman with low back and bilateral leg pain and paresthesia was admitted to our ward. She has a previous medical history of uterine leiomyomas. Magnetic resonance imaging of the lumbar spine revealed vertebral body osteolytic destruction and soft tissue mass in the L4/5 with a secondary lumbar spinal stenosis. Positron emission tomography computed tomography showed moderately intense accumulation of 18F-fluorodeoxyglucose in the L4/5 mass, as well as multiple nodules with increased metabolic activity in both lungs. Diagnoses: Pulmonary and spinal BML. Interventions: The patient underwent a computed tomography-guided percutaneous needle biopsy of the lung nodule and lumbar corpectomy, tumor excision, and vertebroplasty in the L4/5. Outcomes: Pathologically, both pulmonary nodule and vertebral mass were diagnosed as leiomyomas without any malignant evidence. Estrogen and progesterone receptors were both positive in the metastatic tumors. The patient's symptoms completely disappeared after the surgery. The patient is currently receiving outpatient anti-estrogen tamoxifen treatment for a BML. Lessons: Through this case, we suggest that BML should be regarded as part of differential diagnosis in female patients with a previous medical history of uterine leiomyomas presenting with multiple nodules in any parts of the body.